Kontrasepsi dalam Kajian Islam - Gemi Gemi (AL-Fikr, 2013)
The term contraception means the prevention of pregnancy through prevention of conception. There are various ways of contraception, such as contraceptive injections, intravaginal contraceptive, condoms, intrauterine devices (IUD), tubectomy, vasectomy surgery, and alternative conventional means. Contraception methods most widely used today are oral contraceptives and injections. In this context, the substantial function of the Family Planning (KB) program is obviously to lower fertility in order to reduce the burden of nation development in efforts to accomplish contentment and prosperity for the people or nation of Indonesia. As stated in decree number 10 of 1992 on Population Development and Family Welfare Development, the definition of Family Planning is raising efforts and community involvement through maturing age of marriage, birth control, fostering family resilience and family welfare with the purpose of establishing small, happy, and prosperous families.